2014
DOI: 10.1089/end.2013.0794
|View full text |Cite
|
Sign up to set email alerts
|

Early Return of Continence in Patients Undergoing Robot-Assisted Laparoscopic Prostatectomy Using Modified Maximal Urethral Length Preservation Technique

Abstract: MULP rather than PRAS confers higher postoperative CR and shorter time to achieve continence among patients with PCa who underwent RALP without increasing risk of positive margin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 29 publications
1
30
1
4
Order By: Relevance
“…Finally, we did not have a control group. Despite these, our results were superior than those of the series in the literature, and had a new standpoint in detailed anatomy of prostate during RALP [18,23,28]. …”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Finally, we did not have a control group. Despite these, our results were superior than those of the series in the literature, and had a new standpoint in detailed anatomy of prostate during RALP [18,23,28]. …”
Section: Discussioncontrasting
confidence: 74%
“…Hamada et al [18] recently reported their surgical technique for preserving the maximal urethral length. Paparel et al [19] suggested ways of preserving the maximum urethral length during RP for urinary continence.…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8][9] Recent studies reported that preoperative clinical factors, anatomical characteristics, and surgical techniques are significantly associated with urinary incontinence after RARP. 1,7,[10][11][12][13][14][15] Of these factors, membranous urethral length (MUL) is an important factor that directly correlates with the functional sphincter mechanism. The urethral sphincter mechanism is composed of an external striated sphincter and an internal smooth muscle layer that are both crucial to maintaining urethral closure pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Despite technical and methodological improvements in RP, UI does occur and negatively affects quality of life [17]. Assessment of predictors associated with urinary continence has been tried in many studies [7,15,18,19]. This is important for patients and surgeons [18].…”
Section: Discussionmentioning
confidence: 99%